Mush Disaggregation and Dike Propagation Timescales at Active Volcanoes: Evidence from the 2022–2023 Fagradalsfjall Eruptions - Caracciolo, Alberto; Marshall, Edward W.; Mutch, Euan J.F.; Bali, Eniko; Halldórsson, Sæmundur A.; Matthews, Simon; Sigmarsson, Olgeir; Maclennan, John; Merrill, Heini; Gisladóttir, Bryndís Ý.R.; Johnson, Sóley; Kahl, Maren; et al. (Journal of Petrology, 2025)
The architectures of magma plumbing systems and timescales of magmatic processes are fundamental to understanding volcanic eruption dynamics. This is especially crucial when investigating the rejuvenation of magma plumbing system that have been dormant for extended periods, as their long-term evolution is poorly understood, making eruption monitoring more challenging. The 2021–2023 Fagradalsfjall eruptions provide a unique perspective on the initial stages and temporal evolution of a basaltic magma plumbing system, since its previous eruptions occurred ∼7000 years ago. In this study, we focus on the 2022 and 2023 Fagradalsfjall eruptions, integrating our petrological and geochemical dataset with data from the 2021 Fagradalsfjall eruption. We show that the 2022 and 2023 Fagradalsfjall eruptions were sourced from a near-Moho magma domain at ∼14 km depth, similar to the 2021 Fagradalsfjall eruption. However, clinopyroxene–melt barometry suggests that the 2022 and 2023 magmas experienced crystallization in an incipient mid-crustal reservoir or during slow ascent within the magma conduit. The 2022 and 2023 Fagradalsfjall lavas show substantially less compositional variation than the 2021 lavas and are dominated by geochemically enriched compositions that became apparent after the first 40 days of the 2021 event. Olivine mesocrysts (100–500 μm in length) and plagioclase macrocrysts (>500 μm in length) constitute two different populations in the crystal cargo. Olivine mesocrysts are interpreted as autocrysts that crystallized from the host magma, whereas the plagioclase crystals, which are out of chemical equilibrium with the host magma, are derived from a crystal mush. Olivine and plagioclase diffusion timescales represent two different processes. Plagioclase diffusion timescales reveal the erosion of crystal mushes, a process that unfolded over the months and days prior to the 2022 and 2023 eruptions. The decreasing duration of these timescales from 2021 to 2023 suggests an increasingly rapid response of the plumbing system to deep melt injections and the progressive shortening of unrest timescales. In contrast, olivine diffusion timescales capture the timing and duration of dike opening and propagation from near-Moho depths, as evidenced by the correlation between their cumulative frequency distribution and pre-seismic activity. Combined geophysical, petrological, and barometric data suggest that the 2022–2023 propagating dikes took significantly longer to traverse the lower crust and reach mid-crustal levels compared to the upper crust, which they breached within a few days through a fully established magma pathway. Our results highlight the importance of deep magmatic processes and the need to improve monitoring methods for detecting the early stages of magma accumulation and dike propagation at active volcanoes in geological settings similar to Iceland.
CRIS-Team Scopus Importer:2025-06-27
Keywords: Basaltic magma; Diffusion modelling; Fagradalsfjall eruption; Geothermobarometry; Iceland; Petrological monitoring